Regional Muscle Architecture and Bench Press Performance in Paralympic Powerlifting - Marcelo D.M. dos Santos; Bruno F. Rodrigues; Felipe J. Aidar; Lucas T. Lacerda; Andressa Silva; Marco T. Mello; Fernando V. Lima; Mauro H. Chagas; Maicon R. Albuquerque; Rodrigo C.R. Diniz (International Journal of Sports Medicine, 2026)
Abstract This study investigated the magnitude of the association of the regional muscular architecture of the pectoralis major and triceps brachii muscles on the maximum dynamic strength in Paralympic powerlifting athletes. Twenty-six athletes participated in this study. Architectural analysis included cross-sectional area and muscle thickness of the pectoralis major at 15 and 30% of the clavicle length and of the triceps brachii at 50, 60 and 70% of the humerus length, in addition to the pennation angle and fascicle length of triceps brachii at 60%, obtained by panoramic ultrasound. A generalized linear model was used. The significance level was 0.05. The muscle thickness of the pectoralis major at 30% was positively associated with maximum dynamic strength (β=0.2023; p=0.008), for each additional centimeter in the muscle thickness of the pectoralis major, performance is expected to increase by about 56%. The muscle thickness of the triceps brachii at 60% had a significant positive association with performance (β=0.290; p=0.001), corresponding to a potential 34% increase in performance for each centimeter increase. Arm length was negatively associated with performance (β=−0.039; p=0.033), each 1 cm increase in arm length corresponds to an approximately 4% reduction in performance. The muscle thickness of the pectoralis major is the parameter with the greatest magnitude of association with performance.